Regulation of nanoporous structure of detonation nanodiamond powders by pressure: SANS study. Issue 1 (2nd January 2022) - Tomchuk, Oleksandr V.; Avdeev, Mikhail V.; Aksenov, Victor L.; Ivankov, Oleksandr I.; Len, Adél; Turchenko, Vitalii A.; Zabulonov, Yuriy L.; Bulavin, Leonid A.
Abstract: Nanodiamonds combine unique mechanical, thermodynamic and optical properties of diamond with the peculiarities of colloidal dimensions and wide possibilities of chemical modification of their surface. Of particular practical interest is the presence of a branched porous structure inside detonation nanodiamond agglutinates in powders. Application of moderate (up to 1.5 GPa) static pressures allowed us to separate the contributions to small-angle scattering from micro- and nanosized pores. In continuation of the previous studies, the given research shows the possibilities of controlling the fractal structure of the porous system at the nanoscale by applying static pressure. Thus, the partial pore recombination in the pressure range covered leads to the formation of linear pores, in contrast to the branched system characteristic for the initial industrial samples. This modification can have a wide practical impact associated with the loading of anisotropic additives.